Kepastian Hukum Sertifikat Hak Milik Atas Tanah melalui Pendaftaran Tanah Sistematis Lengkap (PTSL) Dikaitkan dengan Sengketa Tanah karena Terdapat Tumpang Tindih - Agus Sugiono; Anriz Nazaruddin Halim; Iran Sahril (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The discussion on the legal certainty of land ownership certificates through complete systematic land registration (PTSL) is related to land disputes due to overlapping. The method used in this study is a normative juridical research type, namely library legal research or secondary data with primary, secondary and tertiary legal sources. Research results The resolution of disputes over overlapping land title certificates from PTSL results can be achieved through non-litigation channels (mediation at the Land Office/BPN) or litigation (lawsuits at the PTUN or District Court). The main steps include checking the validity of the certificate, mediation, and if necessary, cancellation of one of the certificates proven to be administratively flawed. The existence of multiple certificates is a serious problem that directly impacts the legal certainty of land rights. Legal certainty of land rights through PTSL is related to land disputes due to overlapping aims to minimize disputes, but overlapping certificates still occur due to administrative errors, mapping, or inaccurate physical data. Settlement of this dispute requires mediation at the Land Office or a lawsuit to the State Administrative Court (PTUN) for cancellation of the duplicate certificate.